New species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Malawi and South Africa - Hlaváč, Peter; Baňař, Petr (Zootaxa, 2020)
Three new species of Clavigeritae from subsaharan Africa, Zuluclavodes mulanjensis sp. nov., Zuluclavodes minor sp. nov. from southern Malawi and Articerodes jaloszynskii sp. nov. from South Africa, KwaZulu-Natal are described. Diagnosis is provided for both genera, and a key to species is given for the genus Zuluclavodes Hlaváč, 2007. Ischyroceros mirus Reichensperger, 1915 is firstly recorded from Malawi, the illustration of its aedeagus is given. All described species are illustrated and their photos are presented.